Leaching losses and nutrient build-up in the soil through application of raw and digested Palm Oil Mill Effluent (POME) - S., Palaniappan (Universiti Putra Malaysia Press, 1993)
The leaching losses as a result of application of nutrient rich raw and anaerobically digested palm oil mill effluent (POME) onto Segamat Soil Series were studied using lysimeters of 75 cm soil depth. Raw POME was applied at a rate of 1. 78mm rain equivalent per year (rey) / application over 1175 days while anaerobically digested POME was applied at a rate of 3.54 rey/application over 475 days. The average yearly application amounted to 463 mm and 936mm rain equivalent for raw and digested POME respectively. The percentage of nutrients leached as a result of applying raw POME was 49.8% for Ca, 37.7% for K and 7.7% for Mg, while for anaerobically digested POME it was 30.7% for Ca, 16.3% for K and 11.5% for Mg. For both effluent types there was very little leaching of total Nand P.